Toxicity of Neem’s oil, a potential biocide against the invasive Mussel Limnoperna fortunei (Dunker 1857) - Pereyra, Patricio Javier (2012)
The golden mussel Limnoperna fortunei (Dunker 1857) is one of the most distributed Nuisance Invasive Species (NIS) in South America, and a threat of great concern for the industry of the area. In this study, we carried out toxicity tests made with a Neem’s oil solution with L. fortunei larvae and benthonic adults (7, 13 and 19 ± 1 mm). Tests with non-target species (Daphnia magna, Lactuca sativa and Cnesterodon decemmculatus) were also made with the aim to evaluate the potential toxicity of the Neem’s solution in the environment. The LC100 of Neem’s solution obtained for larvae was 500 µl/L, a value much higher than the one obtained for D. magna and C. decemmaculatus. Thus, we recommend that it should not be used in open waters. However, since the adults were killed in 72 h and the larvae in 24 h, this product can be used in closed systems, in man-made facilities.